2023
DOI: 10.3389/fpsyg.2022.1107375
|View full text |Cite
|
Sign up to set email alerts
|

The effect of teaching style and academic motivation on student evaluation of teaching: Insights from social cognition

Abstract: Student evaluation of teaching (SET) is ubiquitous in higher education as a metric for assessing teachers, gaining student feedback, and informing faculty personnel decisions. It is thus imperative to examine the dimensions along which a teacher is judged. This study tested the application of the universal dimensions of social judgment (i.e., warmth and competence) in SET. A total of 108 psychology undergraduates (Mage = 23.63, SDage = 3.14) in Singapore rated a fictitious teacher (i.e., either relationship-or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In addition, research highlights the central role that lecturers play in shaping students' attitudes towards their education [17]. Lecturers' mentoring and teaching styles can have a significant impact on students' perceptions of the relevance of their studies [18], [19], [24].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, research highlights the central role that lecturers play in shaping students' attitudes towards their education [17]. Lecturers' mentoring and teaching styles can have a significant impact on students' perceptions of the relevance of their studies [18], [19], [24].…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that a teacher's style can influence both the learning environment and the perceptions that students have of them. (Keerthigha & Singh, 2023). Although a lot of studies have been conducted on teaching styles, there is a dearth in studies when it comes to "preferred teaching styles" of students.…”
Section: Introductionmentioning
confidence: 99%